USO DO CONCEITO PREVENÇÃO DA POLUIÇÃO NO CONTEXTO DA NORMA ISO 14001: O CASO DA FÁBRICA DE FERTILIZANTES NITROGENADOS DA PETROBRAS - Freitas, Francisco de Assis (2005)
This work intends to discuss how the use of the concept of pollution prevention in the context of the ISO 14001 standard having a continuous improvement as its focus, can get better environmental results for an industrial plant with reflex in the financial aspects. It introduces a case study a Nitrogen Fertilizer Plant, and the results on leading the Environmental Management System in the light of pollution prevention concept. The study is based in the recommendations of the EPA - Environmental Protection Agency, whose principles and objectives is made up of preventing the generation of residues with all its resultant consequences: disposal, treatment, recycling and reduction in its source. One concludes that a management system that uses the ISO 14001 standard and incorporates the logic of pollution prevention concept as a continuous improvement, enables the industries to get tangible results with environmental and financial gains for the activities carried out, as well as intangible results of increasing in the intellectual capital provided by a greater qualification of the people and added value to the society as whole, this one got by means of employees satisfied with their participation in works which enhance the consciousness of the pollution prevention in the productive activities. At the end, all these values sum up in importance to the shareholders and to the society as a whole